2015
DOI: 10.1080/01490400.2014.980591
|View full text |Cite
|
Sign up to set email alerts
|

‘It Doesn't Matter How Big or Small You Are…There's a Position For You’: Body Image Among Female Tackle Football Players

Abstract: The purpose of this study was explore the body image experiences of women who play tackle football. Data included semi-structured interviews with 15 players on a women's tackle football team in Western Canada. Data were analyzed thematically and objectification theory was used to interpret the findings. Themes that emerged included: a) improved body image through physical change, appreciation of function over appearance and shifting ideals of beauty; b) importance of a social atmosphere that celebrated diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 52 publications
(70 reference statements)
1
20
0
4
Order By: Relevance
“…A testkép jellemzően egy hosszabb időszak tekintetében is relatíve stabil (LeCompte et al, 2020), és különböző szinten áll kapcsolatban az önbecsüléssel, érzelmi stabilitással, étkezési szokásokkal, valamint a fizikaiaktivitás-mintázatokkal (Cash et al, 2004). Ugyanakkor több kutatás is alátámasztotta, hogy a fizikai aktivitás, a sport (Cronan-Scott, 2008) testképre gyakorolt hatása csak mérsékelt (Liechty et al, 2015), mégis ezek a tevékenységek a pozitív testkép népszerűsítésében fontos szerepet játszanak (Prichard-Tiggemann, 2005). A pozitív testkép értelmezése esetében a hangsúly a patológiai megközelítésről folyamatosan egy holisztikus, átfogó koncepció irányába tolódott el (Swami et al, 2018).…”
Section: Testkép éS éNképunclassified
See 1 more Smart Citation
“…A testkép jellemzően egy hosszabb időszak tekintetében is relatíve stabil (LeCompte et al, 2020), és különböző szinten áll kapcsolatban az önbecsüléssel, érzelmi stabilitással, étkezési szokásokkal, valamint a fizikaiaktivitás-mintázatokkal (Cash et al, 2004). Ugyanakkor több kutatás is alátámasztotta, hogy a fizikai aktivitás, a sport (Cronan-Scott, 2008) testképre gyakorolt hatása csak mérsékelt (Liechty et al, 2015), mégis ezek a tevékenységek a pozitív testkép népszerűsítésében fontos szerepet játszanak (Prichard-Tiggemann, 2005). A pozitív testkép értelmezése esetében a hangsúly a patológiai megközelítésről folyamatosan egy holisztikus, átfogó koncepció irányába tolódott el (Swami et al, 2018).…”
Section: Testkép éS éNképunclassified
“…Ugyanakkor a fizikai aktivitás és a testkép közötti kapcsolatot az aktivitás típusa, illetve a szabadidős tevékenység tulajdonságai is befolyásolják. Arra vonatkozóan viszont, hogy mely aktivitástípusok segítik elő vagy inkább gátolják ezt a folyamatot, már jóval kevesebb kutatási eredmény áll rendelkezésünkre (Liechty, 2015 év. Szekunder forrásokból ismert (KSH, 2015b), hogy a korcsoportok mentén előrehaladva egyre alacsonyabb a sportolók aránya, melyhez mintánk is alkalmazkodik.…”
Section: Testkép éS a Sport Kapcsolataunclassified
“…Lamb and colleagues 39 examined the health outcomes of sport participation in Britain and found that women who participated in sport had lower blood pressure, lower resting heart rate, lower body mass index, and better perceived health. Liechty and colleagues 40 found that participating in tackle football improved body image among the women who participated. Interestingly, no large-scale studies on the impact of sport on women's health have been conducted in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Some feminist scholars defend group fitness, arguing that instructors can create conditions to empower for women (Haravon Collins, 2002;Liechty et al, 2015;Liimakka, 2011;Markula, 2004a). Consistent with much of the work on leisure constraints to participation in physical activity (e.g., Kennelly et al, 2013;Kim & Trail, 2010;McCarville, 1991), this work on women's group fitness often aims to identify ways to reduce or eliminate constraints to enable participation, with an underlying assumption being that the activity is valuable, such as for its health benefits, and, therefore, should be enabled (e.g., Rich et al, 2019).…”
Section: Introductionmentioning
confidence: 99%